FAKTOR-FAKTOR YANG MEMPENGARUHI TURNOVER INTENTION KARYAWAN PADA PT. MANDIRI TUNAS FINANCE BENGKULU - Andriyani Prawitasari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2016)
Some factors that influenced the turnover intention of employees in PT. Mandiri Tunas Finance Bengkulu. This research was mainly intended to figure out and described some factors that influenced the turnover intention of employees in PT. Mandiri Tunas Finance Bengkulu. Sample of methodthat used in research was purposive convenience sampling. Purposive sampling is the choices of sample based on deliberation, that took based on the goal of research. In this research, that has been of sampling were some of leaders and employees of PT. Mandiri Tunas Finance Bengkulu. Respondence based on deliberation, that for leaders has been worked in PT. Mandiri Tunas Finance Bengkulu since this opened in Bengkulu. Especially for employees, the new employees that joined with this corporation. The result of this research showed that some factors that influenced turnover intention were age, worked period, level of education, loyalty of organization, worked satisfication, and culture that showed in employees of PT. Mandiri Tunas Finance Bengkulu.  Key Word: Turnover Intention